2018
DOI: 10.1039/c8cc01606b
|View full text |Cite
|
Sign up to set email alerts
|

In situ and real-time ToF-SIMS analysis of light-induced chemical changes in perovskite CH3NH3PbI3

Abstract: A hybrid light/ToF-SIMS system was used to analyze the dynamic chemical changes of perovskite CH3NH3PbI3 films under light illumination, in order to reveal the mechanism of light instability for perovskite materials. Real-time material degradation and quasi-reversible iodine migration were successfully observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…However, at lower laser scanning speed, the movement of cations in the perovskite crystal is promoted and concentrated at the defects and grain boundaries, leading to an uneven distribution of the potential field in the MAPbI 3 film and forming a large number of positive and negative electric centers in the film. At the same time, MAPbI 3 perovskite films will decompose to PbI 2 crystals, while MAI will decompose into CH 3 NH 2 and HI (Figure S1a, Supporting Information) . Here we focus on the (110) crystallization peak of the XRD pattern to demonstrate crystal structure changes in the MAPbI 3 perovskite film (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…However, at lower laser scanning speed, the movement of cations in the perovskite crystal is promoted and concentrated at the defects and grain boundaries, leading to an uneven distribution of the potential field in the MAPbI 3 film and forming a large number of positive and negative electric centers in the film. At the same time, MAPbI 3 perovskite films will decompose to PbI 2 crystals, while MAI will decompose into CH 3 NH 2 and HI (Figure S1a, Supporting Information) . Here we focus on the (110) crystallization peak of the XRD pattern to demonstrate crystal structure changes in the MAPbI 3 perovskite film (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…b) TOF‐SIMS 2D images of I − and PbI 3 − acquired after red laser illumination for 0, 10, 15, and 20 min; c) TOF‐SIMS depth profiles of the CH 3 NH 3 PbI 3 film under red laser illumination for 0 (black line), 20 (red line), 40 (blue line), and 60 (green line) min. Inset: the magnified view of PbI 3 − signal changes within the sputter time of 20–80 s. Reproduced with permission . Copyright 2018, The Royal Society of Chemistry.…”
Section: Characterizations Of Ion Migration In Hoip Materials and Devmentioning
confidence: 99%
“…[103] It was also found that the migration of the iodine-related species, which is quasi-reversible, play more important roles under the illumination of light with larger wavelength. [104] In addition, the light with shorter wavelength induces more significant degradation of MAPbI 3 . [104] In device with a TiO 2 layer, the light-induced iodine diffusion into the TiO 2 layer can also lead to the degradation of the TiO 2 layer, limiting the device stability.…”
Section: Light and Temperature Effectsmentioning
confidence: 99%
“…[104] In addition, the light with shorter wavelength induces more significant degradation of MAPbI 3 . [104] In device with a TiO 2 layer, the light-induced iodine diffusion into the TiO 2 layer can also lead to the degradation of the TiO 2 layer, limiting the device stability. [105] ToF-SIMS also revealed that the photovoltaic performance enhancement by light soaking is due to ion redistribution in a solar cell with structure of NiO/perovskite/PCBM, where the light illumination induces MA + accumulation at the perovskite/PCBM interface and I − accumulation at the perovskite/NiO interface, leading to increased open-circuit voltage and fill factor.…”
Section: Light and Temperature Effectsmentioning
confidence: 99%